Biomass estimation models for Acacia saligna trees in restored landscapes - Hagazi, Niguse; Kebede, Mulat; Mokria, Mulugeta; Birhane, Emiru; Gebrekirstos, Aster; Bräuning, Achim (Environmental Research Communications, 2023)
Acacia saligna, originating from Australia, is a naturalized multipurpose tree species widely grown to restore degraded lands of Africa. The contribution of A. saligna in biomass restoration can be quantified using a precise estimation of tree biomass carbon. This study developed species-specific allometric models and evaluated the spatial variation of tree biomass across restored areas in exclosures and open grazing landscapes. These models could play a considerable role in the monitoring of carbon dynamics across A. saligna planation dominated areas. We harvested, excavated, and weighed twenty-one sample trees representing different size classes to develop allometric models for the estimation of aboveground (AGB), belowground (BGB) and total tree (TB) biomass. The average dry-to-fresh mass ratio and the root-to-shoot ratio was 0.47 (±0.13) and 0.28 (±0.14), respectively. Tree biomass significantly correlated with diameter at breast height (r = 0.93; P < 0.001), diameter at stump height (r = 0.88, P < 0.001) and tree height (r = 0.56, P < 0.05). Our best biomass estimation models explained 86%, 82% and 87% of variations in AGB, BGB, and TB, respectively. Models using DSH and DSH & H explained 70%-78% of the variation in AGB, BGB, and TB. Estimated C-stock showed a significant relationship with stem density (R 2 = 0.91, P < 0.01). Estimated TB varied between 1.5-18 Mg ha−1 on grazed land and exclosures. Estimated C-stocks in the exclosure exceeded the estimated C-stock in the open grazing land by ∼60%. This implies that with proper management practices and enrichment planting A. saligna significantly contributes to increasing carbon accumulation on degraded landscapes, playing a key role in climate change mitigation efforts while improving land productivity.
CRIS-Team Scopus Importer:2024-12-16
Keywords: allometric equation; carbon sequestration; climate change; exclosure; restoration; root to shoot ratio